FOUR-FACTOR RESPONSE SURFACE OPTIMIZATION OF THE ENZYMATIC SYNTHESIS OF WAX ESTER FROM PALM KERNEL OIL - Erin Ryantin Gunawan; Dedy Suhendra (Indonesian Journal of Chemistry, 2008)
The synthesis of wax ester using refined, bleached and deodorized (RBD) palm kernel oil (PKO) and oley alcohol catalyzed by Lipozyme IM was carried out. Response surface methodology (RSM) based on a five-level, four-factor central composite rotatable design (CCRD) was used to evaluate the interactive effects of synthesis, of reaction time (5-20 h), temperature (20-50 oC), amount of enzyme (0.1-0.2 g) and substrate molar ratio (palm kernel oil to oleyl alcohol, 1:1-1:5) on the percentage yield of wax esters. The optimum condition conditions derived via RSM were reaction time 8.46 h, temperature 44.4 oC, amount of enzyme 0.182 g, substrate molar ratio 1 to 3.7. The actual experimental yield was 92.9 % under optimum condition, which good accordance to the maximum predicted value of 92.4 %.